(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Professors have long recognized the significance of critical thinking skills as a result of student learning. Critical thinking has recently been identified as one of several learning and innovation skills required to prepare students for postsecondary education and the workforce. Furthermore, the newly developed Common Core State Standards emphasize critical thinking as a cross-disciplinary skill necessary for college and employment. Despite widespread recognition of its importance, there is a notable lack of agreement on how to define critical thinking. The goals of this literature review are to investigate how researchers define critical thinking, investigate how critical thinking develops, learn how teachers can encourage the formation of critical thinking skills in their students, and examine the most effective methods in assessing critical thinking skills.